Association of Positional Plagiocephaly and Developmental Delay Within a Primary Care Network. Issue 2 (February 2021) - Rohde, Jessica F.; Goyal, Neera K.; Slovin, Sara R.; Hossain, Jobayer; Pachter, Lee M.; Di Guglielmo, Matthew D.
ABSTRACT: Objective: Previous research has suggested an association between plagiocephaly and developmental delay. However, study samples drawn from children seen in subspecialty clinics increase the potential for selection and referral bias. Our study evaluates the association between plagiocephaly and developmental delay and the timing of these diagnoses in a primary care setting, where plagiocephaly is commonly diagnosed and managed. Methods: Our retrospective analysis used electronic medical record data from 45 primary care sites within a children's health system from 1999 to 2017, including children aged 0 to 5 years with diagnoses determined by physician diagnosis codes at primary care visits. Children were classified in the plagiocephaly group if diagnosis occurred by 12 months of age. Primary outcome was any developmental delay. Pearson χ 2 test, Fisher exact test, and logistic regression analyses were conducted, with multivariable models adjusted for sex, race, ethnicity, insurance, prematurity status (22–36 weeks' gestation), primary care sites, birth year, and diagnoses of abnormal tone and torticollis. Results: Of 77, 108 patients seen by 12 months, 2315 (3.0%) were diagnosed with plagiocephaly, with an increase in diagnosis prevalence over the study time frame. Plagiocephaly was independently associated with an increased odds of any developmental delay diagnosis (adjusted odds ratio 1.50, 95% confidence interval 1.32–1.70). The diagnosis of plagiocephaly was recorded before the diagnosis of developmental delay in most cases when both diagnoses were present (374 of 404, 92.6%). Conclusion: Data from a large primary care cohort demonstrate an association between plagiocephaly and developmental delay, affirming findings in previous subspecialty literature. Abstract : This article has supplementary material on the web site: www.jdbp.org.